Can Cultural Homogenization be an Open-Ended Process? Reconstructing the Narratives of Brunei’s Homogenization Process - Kumpoh, Asiyah (Journal of Ethnic and Cultural Studies, 2023)
This paper examines the cultural homogenization process in Brunei Darussalam. While the success and outcomes of cultural homogenization, in general, have been thoroughly examined and highlighted, recent research trends have also been focusing more on the processes of cultural homogenization on the ground, i.e., the responses and reactions of ordinary people who are, supposedly, at the receiving end of the homogenization process. In the case of Brunei Darussalam (hereinafter Brunei), cultural homogenization strategies were introduced as early as the 1950s, primarily for state-building purposes. Similar to conventional writings, official narratives of Brunei’s homogenization also focus more on the outcomes of the process. Thus, focusing on the Dusun ethnic group as its case study, this article questions the ways the Dusuns view and respond to the homogenization process. This study utilizes the interview data gathered from thirty-four Dusun respondents to examine how they perceive, understand, and react toward the process and related policies. The findings of the study suggest that the Dusuns generally accept the homogenization with a sporadic indication of contestation mainly due to the observable decline of ethnic culture and language. Modernization has also been identified as a notable agent, integrating successfully with the homogenizing process, and driving the latter to the desired outcomes.